Cytotoxic Activity of Rosa Damascene Mill, Allium sativum, Allium Hirtifolium Boiss, and Prosopis Farcta Extracts on Human Cervical Carcinoma Cell Line - Khadem, Ebrahim; Faghihloo, Ebrahim; Mokhtari-Azad, Talat; Kamalinejad, Mohammad; Pasha Pashabeyg razavi, Kobra; Norouzi, Mehdi (Novelty in Biomedicine, 2019)
Background: Cervical cancer is one of the major reasons of cancer-related mortality. Human papillomavirus is the most common sexually transmitted viral infection, which can lead to cervical cancer. There is no powerful chemotherapeutic agent for HPV infection and cervical cancer. Some plants have the proper potential to be used for treatment of cervical cancer caused by HPV type 18. Materials and Methods: In this study, cytotoxic effect of extract of four indigenous Iranian plants including Rosa damascene mill, Allium sativum, Allium hirtifolium boiss and Prosopis farcta were investigated on the HeLa cell line. HeLa cells were incubated with different concentrations of extracts and then the cell viability was measured by MTT assay. Results: The viable cell numbers were decreased by increase of the extracts concentration. The Allium sativum showed the higher cytotoxicity in all concentrations than the other ones. Afterwards, Allium hirtifolium Boiss, Rosa damascene mill, and Prosopis farcta showed maximum efficiency to decrease cell viability, respectively. Conclusion: The above four mentioned plants might be used for death of HeLa cell harboring HPV type 18. Therefore, they could be employed as a chemotherapeutic agent in the cervical cancer treatment in future.